1989
DOI: 10.1126/science.2667139
|View full text |Cite
|
Sign up to set email alerts
|

Triggering of Allostery in an Enzyme by a Point Mutation: Ornithine Transcarbamoylase

Abstract: The origin of allostery is an unanswered question in the evolution of complex regulatory proteins. Anabolic ornithine transcarbamoylase, a trimer of identical subunits, is not an allosteric enzyme per se. However, when the active-site residue arginine-106 of the Escherichia coli enzyme is replaced with a glycine through site-directed mutagenesis, the resultant mutant enzyme manifests substrate cooperativity that is absent in the wild-type enzyme. Both homotropic and heterotropic interactions occur in the mutan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
28
0

Year Published

1990
1990
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 17 publications
0
28
0
Order By: Relevance
“…Cooperativity can be introduced into the E. coli ATCase catalytic trimer, B. subtilis ATCase, and E. coli OTCase by mutating Arg-105 to Ala, Arg-99 to Ala, and Arg-106 to Gly, respectively (62)(63)(64). Binding of L-ornithine to E. coli OTCase also becomes cooperative when Zn(II) binds to Cys-273 (65)(66)(67).…”
Section: Fig 3 Cartoon Drawings Of E Colimentioning
confidence: 99%
“…Cooperativity can be introduced into the E. coli ATCase catalytic trimer, B. subtilis ATCase, and E. coli OTCase by mutating Arg-105 to Ala, Arg-99 to Ala, and Arg-106 to Gly, respectively (62)(63)(64). Binding of L-ornithine to E. coli OTCase also becomes cooperative when Zn(II) binds to Cys-273 (65)(66)(67).…”
Section: Fig 3 Cartoon Drawings Of E Colimentioning
confidence: 99%
“…Also, tyrosyl-tRNA synthetase from Bacillus stearothermophilus displays a cooperative behavior upon mutation of Lys 233 , involved in the substrate binding, to Ala (4). Furthermore, trimeric aspartate transcarbamoylase from Bacillus subtilis and ornithine transcarbamoylase from Escherichia coli show a homotropic substrate binding behavior upon mutation of Arg 99 and Arg 106 , present at the enzyme active site, to Ala and Gly, respectively (5,6). Also, the homodimeric human glutathione S-transferase P1-1 (GST P1-1), 1 by playing a central role in cellular detoxification processes against toxic and carcinogenic compounds (7,8), displays latent cooperativity.…”
mentioning
confidence: 99%
“…Conceptually, it is easier to understand the creation of homotropic allosteric effects because effector and substrate are one and the same, and thus, effector affinity does not need to evolve: Only allosteric signaling needs to evolve. Accordingly, it has been shown that single point mutations can convert nonallosteric homo-oligomeric enzymes into allosteric enzymes displaying cooperativity involving their substrates (Kuo et al 1989;Scrutton et al 1992;Stebbins and Kantrowitz 1992). However, the creation of heterotropic allostery from proteins that lack effector affinity seems a more difficult task since both effector affinity and an allosteric relationship with the active site must be created.…”
mentioning
confidence: 99%